Deprenyl in the management of response fluctuations in patients with Parkinson's disease on levodopa. - Schachter, M (1980)
Fluctuations in response to levodopa are a common and serious complication of long-term levodopa therapy. It may be possible to prolong the effect of each dose of levodopa by retarding the breakdown of dopamine. The selective monoamine oxidase type B inhibitor deprenyl, which is extensively metabolised to amphetamine and methamphetamine, has this effect as well as possible actions on dopamine release and re-uptake. In a double-blind crossover trial against placebo, deprenyl prolonged the action of levodopa and produced an objective improvement in mobility in five of 10 patients with dose-related response swings, and a subjective improvement in a further four patients. In another group of seven patients with random fluctuations in symptoms, only two noted subjective improvement, and there was an apparent increase in the severity of response swings in five patients. Deprenyl exacerbated dyskinesias, but had no serious side-effects. We conclude that deprenyl is unlikely to benefit patients with random response swings, and may cause deterioration in such cases. However, it may be a useful adjuvant in the management of dose-related response fluctuations in patients already on optional levodopa therapy.